Determining Epidural Catheter Location Using Nerve Stimulation With Radiological Confirmation. Issue 3 (1st May 2000) - Tsui, Ban C.H.; Guenther, Craig; Emery, Derek; Finucane, Brendan
Abstract : Background and Objectives: The use of epidural stimulation to confirm epidural catheter placement has been shown. This case report describes the benefits and problems of using the epidural stimulation test to confirm epidural catheter placement and provides supporting evidence for these observations using radiological imaging. Case Report: Methods: A nerve stimulator was connected to the proximal end of an epidural catheter via an adapter. The cathode lead was connected to the adapter. The anode lead was connected to an electrode placed on the upper extremity as a grounding site. Using 1 to 10 mA current, a segmental motor response indicated that the catheter was in the epidural space. The absence of a motor response indicated that it was not. Cases: In the first patient, the new test predicted subcutaneous epidural catheter placement, which was subsequently confirmed radiologically. In the second patient, the catheter tip was found to be lying near a nerve root, which was again confirmed radiologically. In the third case, a negative test was initially observed with only local muscle movement over the biceps area (T2 ). After relocation of the grounding electrode to the lower extremity, segmental intercostal muscle movement (T4-5 level) was observed. The catheter placement was radiologically shown to be in the T4-5 region. Conclusion: This report illustrates some of the potential benefits and problems of using the nerve stimulation test to confirm epidural catheter placement, with radiological verification.